Empowering Archipelago Regional Laws: A Legal Analysis of Their Role in Promoting Equal Development and Enhancing the Well-being of People in Indonesia: Empowering Archipelago Regional Laws: A Legal Analysis of Their Role in Promoting Equal Development and Enhancing the Well-being of People in Indonesia - Jayawibawa, Marcellus Hakeng (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
The Unitary State of the Republic of Indonesia is an archipelagic state characterized by the Archipelago with territories whose boundaries and rights are stipulated by law with the presence of the Archipelago Regional Bill, accessibility to fulfilling basic needs, such as good education and health, as well as productivity of small islands, coastal investment, and economic independence of coastal communities can be realized. The Bill on the Archipelago Region is considered to be able to assist the region in efforts to alleviate poverty and equalize social justice for all Indonesian people who live in archipelagic areas also as a legal design to answer various problems in the archipelago: poverty, inequality, and underdevelopment of national development. The importance of Indonesia having an Archipelagic Regional Law is to develop maritime potential, can accelerate infrastructure development and equitable distribution of development in realizing the welfare of the Indonesian people are Adequate protection of their rights and the surrounding environment,Overcoming resource conflicts,Economic and social development, Overcome environmental damage, Improving understanding of the importance of managing islands, Resolving and anticipating regional disparities in the archipelago, to formulate Local Own Revenue